KEPEMIMPINAN ROHANI YANG EFEKTIF: SEBUAH KAJIAN EKSEGESIS KELUARAN 18 : 13 – 27 DAN SUMBANGANNYA BAGI MASA KINI - Widianto, Alwi (TEOLOGIS, RELEVAN, APLIKATIF, CENDIKIA, KONTEKSTUAL, 2023)
Moses is one of the leaders described in the Bible. In the chiastically arranged section of Exodus 18:13-27, Jethro provides an assessment of Moses' ineffective leadership methods. Jethro also suggested that Moses apply a tiered leadership model, in order to make his duties easier. Apart from that, Jethro also proposed four basic requirements for the leaders who would be appointed by Moses, namely: competent, fearing God, trustworthy, and hating the pursuit of bribes. From these two suggestions, Jethro also added that problems should be categorized by distinguishing between large and small matters. Even though Jethro's three suggestions come from a Bible story written thousands of years ago, they are still relevant in the current context, especially for carrying out effective spiritual leadership.